Common Defects and Structural Problems in the Buildings of Northern Cyprus, their Reasons and Prevailing Applicable Solutions - Akilah, Mohammed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
In the recent years, building sector grows rapidly parallel to the human needs. Sometimes these quick productions cause several types of problems on the buildings. These problems occur in varying intensities depending on the type, location, environment, materials and the construction conditions of the building. Problems and failures in buildings can be broadly attributed to either defects, deteriorations or structural problems. Mostly, these defects or structural problems arise due to error or omission that is breach of contract or negligence by designer, contractor, or user. In general, lack of care and knowledge in specification or workmanship are the main reasons of various defects and structural problems. On the other hand, deterioration is natural process, which may be unavoidable, although minimized by care in design and the selection of materials. Cracks, efflorescence, peeling on painting, mouldiness, rising dampness, soft storey, short column, shear cracks, compression cracks, irregularities in plan, irregularities in elevation and etc. are some of the most significant problems that occur in building of Northern Cyprus. These defects, deteriorations and structural problems have negative effects both on human and building lives. They mostly harm to the health and economy. Besides, they reduce the aesthetic quality. On this basis, the aim of the study is to discuss these prevailing defects and structural problems with their reasons which occur in North Cyprus. It is also expected to present the most common precautions and available applied methods for preventing or reducing these problems. Work to be carried out: 1. General search about the building defects and structural problems and categorization. 2. According to the first step (researches), the most common precautions and available applied methods for preventing or reducing these defects and structural problems were investigated and presented. 3. Case studies in different districts of North Cyprus were visited and the collected data were analysed and compared. There are a total of 125 case studies in this thesis divided into two samples. The first sample represents completed buildings contains 100 case studies consisting of 25 case studies for each of the four following districts: Mağusa, İskele, Lefkoşa and Girne. This sample is aimed for the study of reinforced concrete defects and non-structural defects. The second sample represents buildings under construction contains 25 case studies. This sample is aimed for the study of seismic design faults.

ÖZ: Son yıllarda, inşaat sektörü insanların ihtiyaçlarına paralel olarak hızla büyümektedir. Bazen bu hızlı büyüme, binalarda çeşitli sorunlara sebep olmaktadır. Bu sorunlar, binanın tipi, konumu, kullanılan malzeme, çevre koşulları ve binanın yapım şartlarına bağlı olarak değişen seviyelerde meydana gelmektedir. Binalardaki problemler, kusurlara, bozulmalara ve/veya yapısal sorunlara dayanır. Çoğunlukla, bu kusurlar ve yapısal sorunlar tasarımcının, yüklenicinin ve/veya kullanıcının ihmali nedeniyle ortaya çıkar. Genel olarak, ihmal, şartnamelerle ilgili bilgi eksikliği veya işçilik problemleri binalardaki kusurlar ve yapısal sorunların ana nedenleridir. Öte yandan, binalardaki problemler, tasarım, periyodik bakım ve doğru malzeme seçimi ile minimize edilse de doğası gereği tamamen engellenemeyebilir. Çatlaklar, çiçeklenme, boyada soyulma, küf, zeminden yükselen nem, yumuşak kat, kısa kolon, kesme kuvveti çatlakları, basınç çatlakları, planda düzensizlik durumları, düşey doğrultuda düzensizlik durumları gibi sorunlar Kuzey Kıbrıs’ta bulunan binalarda meydana gelen en önemli sorunlar arasında yer almaktadır. Bu kusurların, bozulmaların ve yapısal problemlerin insan sağlığı ve binaların ömrü üzerinde olumsuz etkileri vardır. Çoğunlukla da sağlık ve ekonomiye zarar vermektedirler. Bunun yanında, binalardaki estetik kalitesini de düşürmektedirler. Bu temele dayanarak, çalışmanın amacı Kuzey Kıbrıs’taki yapılarda meydana gelen bu problemleri ve sebeplerini ortaya koymaktır. Buna ek olarak seçilen vaka incelemeleriyle, bu problemlerin önlenmesi veya azaltılmasına yönelik çözüm önerileri ve metotlarını sunmaktır. Gerçekleştirilecek çalışmada: 1. Bina kusurları, yapısal sorunlar ve bunların sebepleri ile ilgili detaylı bilgi verilmesi. 2. İlk adımda yapılan araştırmalar ışığında, bina problemlerinin önlenmesi veya azaltılması için gerekli çözüm önerileri ve metotlarını araştırmak ve sunmak. 3. Kuzey Kıbrıs'ın farklı şehirlerindeki (Mağusa, İskele, Lefkoşa ve Girne) yapılardan örnekler seçilerek incelenmesi ve toplanan verilerin analiz edilmesi ve karşılaştırılması. Bu tez kapsamında toplam 125 örnek vaka incelenmiştir. İlk 100 vaka çalışmasında her şehirden (Mağusa, İskele, Lefkoşa ve Girne) 25 bina seçilerek betonarme kusurları ve yapısal olmayan problemler incelenmiştir. Geriye kalan 25 bina yine bu şehirlerden ve yapım aşamasındaki binalardan seçilerek sismik tasarım hataları incelenmiştir.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2017. Supervisor: Assoc. Prof. Dr. Giray Özay.
Keywords: Civil Engineering; Buildings--Defects--Building materials--Defects--Building failures--Buildings, Repair and reconstruction--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Building Defects; Deteriorations; Structural Problems; Seismic Design; Northern Cyprus